Treatment Optimization in Multiple Sclerosis: Canadian MS Working Group Recommendations. (6th July 2020) - Freedman, Mark S.; Devonshire, Virginia; Duquette, Pierre; Giacomini, Paul S.; Giuliani, Fabrizio; Levin, Michael C.; Montalban, Xavier; Morrow, Sarah A.; Oh, Jiwon; Rotstein, Dalia; Yeh, E. Ann
Abstract: The Canadian Multiple Sclerosis Working Group has updated its treatment optimization recommendations (TORs) on the optimal use of disease-modifying therapies for patients with all forms of multiple sclerosis (MS). Recommendations provide guidance on initiating effective treatment early in the course of disease, monitoring response to therapy, and modifying or switching therapies to optimize disease control. The current TORs also address the treatment of pediatric MS, progressive MS and the identification and treatment of aggressive forms of the disease. Newer therapies offer improved efficacy, but also have potential safety concerns that must be adequately balanced, notably when treatment sequencing is considered. There are added discussions regarding the management of pregnancy, the future potential of biomarkers and consideration as to when it may be prudent to stop therapy. These TORs are meant to be used and interpreted by all neurologists with a special interest in the management of MS.